Seismic anisotropy in deforming halite: evidence from the Mahogany salt body - Prasse, P; Wookey, J; Kendall, JM; Roberts, D; Dutko, M (Oxford University Press, 2020)
We present unambiguous evidence that the Mahogany salt body, located in the Northern part of the Gulf of Mexico, is seismically anisotropic. Evidence of anisotropy comes from shear wave splitting data obtained from a vertical seismic profile VSP. The data set consists of 48 vertically aligned receivers in a borehole drilled through the salt body. Splitting analysis is performed on shear wave phases that are converted from compressional waves at the top and bottom of the salt body. The phase converted at the top of the salt layer shows a clear signature of seismic anisotropy, while the phase at the base of the salt layer shows negligible splitting. We investigate the possibility of rock salt halite LPO as a cause of the observed anisotropy. A finite element geomechanical salt deformation model of the Mahogany salt body is developed, where deformation history is used as an input to the texture plasticity simulation program VPSC. Assuming a halite salt body, a full elasticity model is then calculated and used to create a synthetic VSP splitting data set. The comparison between the synthetic and real VSP data set shows that LPO of rock salt can explain the observed anisotropy remarkably well. This is the strongest evidence to date of seismic anisotropy in a deforming salt structure. Furthermore, for the first time, we are able to demonstrate clear evidence that deforming halite is the most likely cause of this anisotropy, combining data set analysis and synthetic full wave form modelling based on calculated rock salt elasticities. Neglecting anisotropy in seismic processing in salt settings could lead to potential imaging errors, for example the deformation models show an averaged delta parameter of δ=-0.06, which would lead in a zero offset reflection setting to a depth mismatch of 6.2 per cent. Our work also show how observations of salt anisotropy can be used to probe characteristics of salt deformation.